Aldehyde Dehydrogenase 1 Is a Marker for Normal and Malignant Human Colonic Stem Cells (SC) and Tracks SC Overpopulation during Colon Tumorigenesis - Huang, Emina H. (2009)
Although the concept that cancers originate from stem cells (SC) is becoming scientifically accepted, mechanisms by which SC contribute to tumor initiation and progression are largely unknown. For colorectal cancer (CRC), investigation of this problem has been hindered by a paucity of specific markers for identification and isolation of SC from normal and malignant colon. Accordingly, aldehyde dehydrogenase 1 (ALDH1) was investigated as a possible marker for identifying colonic SC and for tracking them during cancer progression. Immunostaining showed that ALDH1(+) cells are sparse and limited to the normal crypt bottom, where SCs reside. During progression from normal epithelium to mutant (APC) epithelium to adenoma, ALDH1(+) cells increased in number and became distributed farther up the crypt. CD133(+) and CD44(+) cells, which are more numerous and broadly distributed in normal crypts, showed similar changes during tumorigenesis. Flow cytometric isolation of cancer cells based on enzymatic activity of ALDH (Aldefluor assay) and implantation of these cells in nonobese diabetic–severe combined immunodeficient mice (a) generated xenograft tumors (Aldefluor(−) cells did not), (b) generated them after implanting as few as 25 cells, and (c) generated them dose dependently. Further isolation of cancer cells using a second marker (CD44(+) or CD133(+) serially) only modestly increased enrichment based on tumor-initiating ability. Thus, ALDH1 seems to be a specific marker for identifying, isolating, and tracking human colonic SC during CRC development. These findings also support our original hypothesis, derived previously from mathematical modeling of crypt dynamics, that progressive colonic SC overpopulation occurs during colon tumorigenesis and drives CRC development.